REFORM THOUGHTS IN TAFSIR AL-MARAGHI BY SHAYKH AHMAD MUSTAFA AL-MARAGHI - Yahaya, Amiratul Munirah (Online Journal of Research in Islamic Studies, 2017)
The Tafsir al-Maraghi written by Shaykh Ahmad Mustafa al-Maraghi (1883-1952) was greatly influenced by ‘Abduh approach known al-Adab wa al-Ijtima’i (literature and social) which was initially applied in Tafsir al-Manar. It is apparent that al-Maraghi’s thoughts was influenced by the thoughts of his teachers Shaykh Muhammad ‘Abduh and Sayyid Muhammad Rasyid Rida. This article examines the reform thoughts of Shaykh Ahmad Mustafa al-Maraghi in his great work Tafsir al-Maraghi. Al-Maraghi’s thoughts encompasses the modern-day life practices of faith, politics, social and economics. His ideas for reform is based on the teachings of the Quran as guidance in life, and his thoughts can be applied in many aspects of human capital development.